O estudo prévio de impacto de vizinhança e seus limites, no caso-referência do Município do Rio de Janeiro - David, Monique Abreu (2009)
This work evaluates the Preview Study of Neighborhood Impact, as an instrument of Urban Policy, set forth in Federal Law # 10.257/2001 (City Statute Estatuto da Cidade), and its limits in the case reference of the city of Rio de Janeiro. As a consequence of this analysis, we will discuss the Movements in favor of Urban Reform and the advances of Urban Policy as a result of the Federal Constitution of 1988. Within this perspective, we will also analyze the local jurisdictions and the sharing of the jurisdictions as set forth in the Federal Constitution of 1988. The Preview Study of Neighborhood Impact will be analyzed from the edition of the City Statute (Federal Law # 10.257/2001), taking into account the local jurisdiction to legislate for the subject and the historical evolution of the Statute, comparing it with the Preview Study of Environmental Impact; and outlining a reflection on the legislative proposal of regulation of the institution in the case-reference of the city of Rio de Janeiro. The limits of the Preview Study of Neighborhood Impact, not yet regulated by the city of Rio de Janeiro, as well as the analysis of the proposal of regulation through the Project of Law # 303/2001, are the general purposes of this work. The limits of the incidence of the Preview Study of Neighborhood Impact is due, in great part, to the lack of legislative regulation of the institution and it is encomtering difficulties to become effective for reasons which will be analyzed and discussed in this work.